1999
DOI: 10.1128/jcm.37.8.2592-2597.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel Mycobacterium avium Allelic Variants in Pig and Human Isolates from Brazil by PCR-Restriction Enzyme Analysis

Abstract: Mycobacterium avium complex (MAC) is composed of environmental mycobacteria found widely in soil, water, and aerosols that can cause disease in animals and humans, especially disseminated infections in AIDS patients. MAC consists of two closely related species, M. avium and M. intracellulare, and may also include other, less-defined groups. The precise differentiation of MAC species is a fundamental step in epidemiological studies and for the evaluation of possible reservoirs for MAC infection in humans and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…In contrast to previously reported results, based on IS 1245 RFLP patterns (de Smet et al , 1995; Leao et al , 1999), the majority of the Mav III Colombian isolates showed a single copy of each IS 1245 and IS 1311 . This unique characteristic prompted analysis of the corresponding insertional loci of these two insertion sequence (IS) in the bacterial genome.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previously reported results, based on IS 1245 RFLP patterns (de Smet et al , 1995; Leao et al , 1999), the majority of the Mav III Colombian isolates showed a single copy of each IS 1245 and IS 1311 . This unique characteristic prompted analysis of the corresponding insertional loci of these two insertion sequence (IS) in the bacterial genome.…”
Section: Introductioncontrasting
confidence: 99%
“…The identification of MA PRA variants was based on the results of PRA using the primers Tb11 and Tb12, to amplify a 441‐bp fragment of the hsp 65 gene and the PRA profiles were analysed according to the procedure described by Telenti et al (1993). Profiles were further identified according to algorithms previously described in the literature (Devallois et al , 1997; da Silva Rocha et al , 1999; Leao et al , 1999). The sequencing of the amplified products was also performed for a more complete characterization and to confirm the restriction sites, using an automated sequencer (Applied Biosystems 3730).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 16S rDNA sequence is considered as the molecular ' gold standard ' for mycobacterial species identification ; a highly polymorphic region has been shown to contain species-specific DNA polymorphisms (Bo$ ddinghaus et al, 1990 ;Kirschner et al, 1993a). However, other semi-conserved genes, like hsp65 (Devallois et al, 1997 ;Lea4 o et al, 1999 ;Swanson et al, 1997 ;Telenti et al, 1993) and rpoB (Kim et al, 2001), and the 16S-23S rDNA internally transcribed spacer (ITS) region (Abed et al, 1995 ;Barry et al, 1991 ;Glennon et al, 1994 ;Portaels et al, 1996 ;Roth et al, 1998) have been shown to be more discriminating. The 16S-23S rDNA ITS sequence can be used to distinguish between the species M. avium and M. intracellulare.…”
mentioning
confidence: 99%